Dance: a cultural mediation power in school (Research, Society and Development, 2021)
This article is about cultural mediation through dance. The objective is to discuss how dance can enhance cultural mediation at school. It is a qualitative study, and used the Discursive Textual Analysis methodology for data analysis, which was treated from the analysis of photographs. The article discusses Cultural Mediation, Spaces and Objects; Aesthetic Education and Experience. As a result, it is signaled that mediation in dance makes it possible to look at this art beyond a physical activity, as well as the simple construction of a choreography; it instigates students to realize their potential for movement and relationships with themselves, with the world, and everything and everyone who is close to them, and enables the emergence of sensitivity and perception in communion with reason. Dance at school is an affecting power when developed through experimenting, aesthetic education and cultural mediation.